Diabetes Attitudes, Wishes and Needs second study (DAWN2™): Cross‐national benchmarking of diabetes‐related psychosocial outcomes for people with diabetes. Issue 7 (23rd June 2013) - Nicolucci, A.; Kovacs Burns, K.; Holt, R. I. G.; Comaschi, M.; Hermanns, N.; Ishii, H.; Kokoszka, A.; Pouwer, F.; Skovlund, S. E.; Stuckey, H.; Tarkun, I.; Vallis, M.; et al.
Abstract Aims The second Diabetes Attitudes, Wishes and Needs (DAWN2) study aimed to assess psychosocial outcomes in people with diabetes across countries for benchmarking. Methods Surveys included new and adapted questions from validated questionnaires that assess health‐related quality of life, self‐management, attitudes/beliefs, social support and priorities for improving diabetes care. Questionnaires were conducted online, by telephone or in person. Results Participants were 8596 adults with diabetes across 17 countries. There were significant between‐country differences for all benchmarking indicators; no one country's outcomes were consistently better or worse than others. The proportion with likely depression [WHO‐5 Well‐Being Index (WHO‐5) score ≤ 28] was 13.8% (country range 6.5–24.1%). Diabetes‐related distress [Problem Areas in Diabetes Scale 5 (PAID‐5) score ≥ 40] was reported by 44.6% of participants (17.2–67.6%). Overall quality of life was rated 'poor' or 'very poor' by 12.2% of participants (7.6–26.1%). Diabetes had a negative impact on all aspects investigated, ranging from 20.5% on relationship with family/friends to 62.2% on physical health. Approximately 40% of participants (18.6–64.9%) reported that their medication interfered with their ability to live a normal life. The availability of person‐centred chronic illness care and support for active involvement was rated as low. Following self‐care advice for medication and diet was most common, and least common for glucose monitoring and foot examination, with marked country variation. Only 48.8% of respondents had participated in diabetes educational programmes/activities to help manage their diabetes. Conclusions Cross‐national benchmarking using psychometrically validated indicators can help identify areas for improvement and best practices to drive changes that improve outcomes for people with diabetes.